Critical Review of the Challenges Faced by Nurses and Emergency Medical Services Teams in Multi-Casualty Incidents - Al Ashwi , Sultan Saleh S; AI-Dhaen , Saleh Ali S; AL Rasheid , Abdulrahman Mesfer S; Lasloom, Hadi Saker S; Alhabis , Raed Mohammed R; Almansour , Fehaid Saleh M; Al-Harith , Mohammed Mana H; AL- Alhareth , Mohammed Yahya A; Al Yami, Adal Mohammad; Al Kharsan , Hussain Muteb H; Al Yami , Misfer Haasan; Al-Yami , Saleh Ali H; et al. (Journal of Ecohumanism, 2024)
Mass-casualty events, or MCIs, pose various problems to healthcare institutions around the world, especially to nurses and the services of EMS in satisfying the prompt and integrated needs of traumatized or diseased individuals. This review discusses the organizational, psychological, and systems challenges that such professionals encounter. Based on case studies, literature reviews, and survey data, the study presents and emphasizes such problems as the lack of training, the scarcity of materials, the psychological effects, and failures in communication with patients. Implication measures are provided for refocusing response systems, optimal distribution of resources, and coping with the mental health of first responders.